Amicable sets of matrices and their applications in constructing orthogonal designs and self-dual codes - Georgiou S; Koukouvinos C. (Utilitas Mathematica, 2007)
In this paper, sets of eight circulant amicable matrices and a class of two-variable orthogonal designs are combined to generate some suitable arrays and infinite families of orthogonal designs. It is also illustrated how this method can be used to construct some new orthogonal designs and self-dual codes over some prime fields.